RESPON PERKECAMBAHAN BENIH KOPI PADA BERBAGAI TINGKAT KEMASAKAN BUAH DENGAN APLIKASI ZAT PENGATUR TUMBUH - Farida Farida (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2018)
The growth responses of the coffee seeds toward of fruit maturity and application of plant growth regulators was conducted to determine effect of fruits maturity, the effect of application of plant growth regulators, and the interaction of both factors toward germination and growth of coffee seeds. This research obtained for three mounth on January to Aprl 2018. The research was conducted in Kabo Street, Mulia 6, Swarga Bara Village Sangatta Sub-distrct East Kutai. This research uses is Completely Randomized Design (CRD) of factorial experiments each of three treatment factorial. First factor is fruit maturity (B) are : B1 = brown, B2 = red, B3 = orange. Second factor is application of plant growth regulators (T) are T1 = 100 mgL-1,  T2 = 150 mgL-1,  T3 = 200 mgL-1. The research result to showed was interacton of red fruit maturity and 1500 mgL-1 of plant growth regulators (B2T2) giving are effected significantly of increasing parameter on germination percentase is 100,00%, time germination is 18,233 days, , and index vigor is 0,605, roots long is 7,080 cm, and plant long is 7,707 cm.